2021
DOI: 10.1002/humu.24243
|View full text |Cite
|
Sign up to set email alerts
|

Global spectrum of population‐specific common missense variation in cytochrome P450 pharmacogenes

Abstract: Next‐generation sequencing technology has afforded the discovery of many novel variants that are of significance to inheritable pharmacogenomics (PGx) traits but a large proportion of them have unknown consequences. These include missense variants resulting in single amino acid substitutions in cytochrome P450 (CYP) proteins that can impair enzyme function, leading to altered drug efficacy and toxicity. While most unknown variants are rare, an overlooked minority are variants that are collectively rare but enr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 74 publications
0
2
0
Order By: Relevance
“…5). Functional CYP variants are known to be unequally distributed amongst the world populations 9,54 and here we found that this variant is more common in the East Asian or Chinese populations but its effects on drug metabolism remain unreported. If the variant effect is substrate-speci c, potential drug-drug interactions involving CYP2D6 substrates may arise if the drug has a stronger a nity for the enzyme than concomitantly administered CYP2D6 substrates.…”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation
“…5). Functional CYP variants are known to be unequally distributed amongst the world populations 9,54 and here we found that this variant is more common in the East Asian or Chinese populations but its effects on drug metabolism remain unreported. If the variant effect is substrate-speci c, potential drug-drug interactions involving CYP2D6 substrates may arise if the drug has a stronger a nity for the enzyme than concomitantly administered CYP2D6 substrates.…”
Section: Discussionmentioning
confidence: 61%
“…Annotation and prediction of population-speci c effects on drug binding is invaluable for drug development efforts which can study and address such effects early in the development pipeline avoiding costly surprises at later stages [36][37][38] . This especially includes effects in the important CYP family of drug metabolizing enzymes 39 .…”
Section: Mapping Variants To Structuresmentioning
confidence: 99%